On the accessible reaction channels of vinyl gold(I) species: π- and [sigma]-pathways - Nunes dos Santos Comprido, Laura; Klein, Johannes E. M. N.; Knizia, Gerald; Kästner, Johannes; Hashmi, A. Stephen K. (Chemistry - a European journal, 2017)
The potential of vinyl Au species to react either through a controlled π- or σ-pathway is demonstrated. This nomenclature is directly derived from the orbitals of the vinyl Au species leading to the newly formed bonds. When the π-bond of the vinyl Au intermediate is transformed into a σ-bond, we name it π-pathway, and a σ- to σ- transformation is named σ-pathway. Examples of reactions following these pathways are a Au-catalysed [3,3]-sigmatropic rearrangement and a protodeauration reaction. These reactions have been studied using intrinsic bond orbitals (IBOs) and allow for the clear identification of these pathways. Energies for the reaction path of the Au-catalysed [3,3]-sigmatropic rearrangement were in addition computed using CCSD(T)-F12. Analysis of the intrinsic reaction coordinate (IRC) of the [3,3]-sigmatropic rearrangement using IBOs further allows us to refine the previous mechanistic proposal and identifies a hidden intermediate along the reaction path.